One-stop interventional procedure for bicuspid aortic stenosis in a patient with coexisting aortic coarctation: a case report - He, Xingwei; Dhuromsingh, Menaka; Liu, Wanjun; Zhou, Qiang; Zeng, Hesong (Frontiers in Cardiovascular Medicine, 2023)
Introduction Coarctation of the aorta (CoA) is usually diagnosed and corrected early in life. Most untreated patients with CoA usually die before 50 years of age. Adult patients with concomitant CoA and severe bicuspid aortic stenosis are relatively rare and present complex management challenges without standard guidelines. Case summary A 63-year-old female patient with uncontrolled hypertension was admitted due to chest pain and dyspnea upon exertion (NYHA grades III). Echocardiogram showed a severely calcified and stenotic bicuspid aortic valve (BAV). A severe stenotic calcified eccentric aortic coarctation 20 mm distal to the left subclavian artery (LSA) was discovered by computed tomography (CT) angiography. Following consultation with the cardiac team and patient willingness, we performed a one-stop interventional procedure to repair both defects. First, a cheatham-platinum (CP) stent was implanted via the right femoral access, immediately distal to the LSA. Due to the markedly twisted and angled descending aortic arch, we chose to perform transcatheter aortic valve replacement (TAVR) via the left common carotid artery. The patient was discharged and followed up for 1 year without symptoms. Discussion Although surgery is still the main treatment for these diseases, it is not suitable for high-risk surgical patient. Transcatheter intervention for patients with severe aortic stenosis complicated with CoA simultaneously is rarely reported. The success of this procedure depends on the patient's vascular condition, the skills of the heart team, and the availability of the technical platform. Conclusion Our case report demonstrates the feasibility and efficacy of a one-stop interventional procedure in an adult patient with concurrent severely calcified BAV and CoA via two different vascular approaches. Transcatheter intervention, in contrast to traditional surgical approaches or two-stop interventional procedures, as a minimally invasive and novel method, offers a wider range of therapeutic methods for such diseases.